2022
DOI: 10.1111/ced.15341
|View full text |Cite
|
Sign up to set email alerts
|

Menopause, skin and common dermatoses. Part 4: oral disorders

Abstract: The physiological impact of declining oestrogen levels during menopause has been well documented. We conducted a literature review to assess the impact of menopause on oral health. Falling oestrogen levels are associated with adverse effects on the gingival, oral and buccal epithelia. The symptoms prevalent in perimenopausal and postmenopausal women range from dry mouth to immune-mediated mucocutaneous disease and burning mouth syndrome. Our review has highlighted the need for further research into potential t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The decrease in collagen in women is calculated at 2.1% per year [5,61]. These variations cause various atrophies, which not only concern the genitourinary system but also the skin in general, becoming less elastic and dehydrated; this causes an increase in wrinkles and itchy sensations, and arthralgia also occurs at the distal joints (knees, hip, and spine); the incidence is 50% [11,62]. Many studies have shown that with the hormonal changes of menopause, sexual desire in women decreases.…”
Section: Menopause-associated Symptoms and Diseasesmentioning
confidence: 99%
“…The decrease in collagen in women is calculated at 2.1% per year [5,61]. These variations cause various atrophies, which not only concern the genitourinary system but also the skin in general, becoming less elastic and dehydrated; this causes an increase in wrinkles and itchy sensations, and arthralgia also occurs at the distal joints (knees, hip, and spine); the incidence is 50% [11,62]. Many studies have shown that with the hormonal changes of menopause, sexual desire in women decreases.…”
Section: Menopause-associated Symptoms and Diseasesmentioning
confidence: 99%
“…We also identified that the majority of BMS patients were women. The age and sex characteristics of BMS hint at two main points: (1) age and body changes that could include the susceptibility to dry skin by the nature of decreased water content and overall drier skin [52] and (2) hormonal changes during the menopausal years of the affected women [53]. Lower estrogen levels could lead to not only skin dryness and thinning but also other skin concerns, such as decreased skin elasticity, firmness, wrinkles, and age spots [54].…”
Section: Demographic Characteristicsmentioning
confidence: 99%